The Palestinian Hamas vision, violence, and coexistence - Mishal, Shaul 1945- (Columbia University Press, 2006)
Shows how Hamas is essentially a social and political movement that provides community services and responds to political realities through bargaining and power brokering. This book lifts the veil on Hamas' strategic decision-making methods during the Intifada and the struggle with the PLO.